The effect of probiotic supplementation on perceived stress and bowel function in healthy young adults: evidence from a randomized controlled trial in Makkah - Noorwali, Essra A.; Aljaadi, Abeer M.; Abusudah, Wafaa F.; Bakhdar, Fatmah A.; Bin-Ali, Dania H.; Alshinawi, Amani; Bawazir, Asma; Mutlaq, Raghad A.; Maimany, Heba A.; Barnawi, Layan A.; Murshed, Bshayer; Aljared, Bayan; et al. (Frontiers in Nutrition, 2026)
BackgroundYoung adults experience high, persistent stress due to academic, social, and financial pressures. Lactobacillus rhamnosus GG (LGG) may reduce stress via the gut–brain axis, yet evidence from Middle Eastern populations is limited. We tested whether LGG lowers perceived stress in Saudi young adults and improved bowel function.MethodsIn this randomized controlled trial, healthy adult participants with moderate–high Perceived Stress Scale (PSS) scores received LGG (6 × 109 CFU/day, capsule) for 30 days or no intervention. Validated PSS version, anthropometrics and bowel habits were assessed at baseline and endline. Analyses included paired, two-sample t tests, Wilcoxon rank-sum and multivariable linear regression adjusted for baseline PSS, age, sex, and BMI were conducted.ResultsSixty-six participants completed the trial (37 probiotic; 29 controls; mean age 21.97 ± 2.59 vs. 20.83 ± 1.91 years). Post-intervention, stress score reductions were significantly greater in the probiotic group than controls (p = 0.006). In sex-stratified analyses, males receiving probiotics showed larger reductions than male controls (p = 0.007), while no significant difference was observed among females (p = 0.341). Probiotic participants also reported lower post-intervention stress scores (14.81 ± 6.12 vs. 19.48 ± 5.91; p = 0.003) and a higher proportion classified as low stress (84.2% vs. 15.8%; p = 0.008). Adjusted models showed control participants had stress scores 3.79 points higher than probiotic recipients (95% CI 0.74–6.83; p = 0.016). No between-group differences were found in bowel movement frequency, consistency, or GI symptom improvement.ConclusionA 30-day LGG course may reduce perceived stress—particularly in males—with a trend level effect observed in females without affecting bowel habits. Probiotics may be considered as an adjunct for stress management in high-risk young adult populations. Future larger, placebo-controlled, and longer-term trials are recommended to confirm these findings and explore underlying mechanisms.Clinical trial registrationThis trial is registered at ClinicalTrials.gov (Identifier: NCT06464484; https://clinicaltrials.gov/study/NCT06464484).